A Distinct Tobamovirus Associated With Trichosanthes kirilowii Mottle Mosaic Disease - Chen, Cheng; Du, Min; Peng, Deliang; Li, Wulun; Xu, Jingfeng; Yang, Xiuling; Zhou, Xueping (Frontiers in Microbiology, 2022)
Trichosanthes kirilowii is one of the most important perennial herbaceous vines that have been used in traditional Chinese medicine. In this study, a novel RNA virus was discovered in T. kirilowii plants showing leaf mottling and mosaic symptoms. The complete genome of this virus is 6,524 nucleotides long and encodes four open reading frames (ORFs) which are arranged in a manner typical of tobamoviruses. Phylogenetic analysis based on the complete genome sequence revealed that the virus was clustered into a branch with the tobamoviruses whose natural host are plants belonging to the family Cucurbitaceae. A full-length infectious cDNA clone was then constructed and demonstrated to establish a systemic infection with typical symptoms in Nicotiana benthamiana, T. kirilowii, and five other cucurbitaceous crops including Cucumis melo, C. lanatus, C. sativus, Luffa aegyptiaca, and Cucurbita pepo via agrobacterium-mediated infectivity assays. Further experiments provided evidence that the rod-shaped viral particles derived from the infectious clone could be mechanically transmitted and reproduce indistinguishable symptoms in the tested plants. Taken together, the mottle mosaic disease of T. kirilowii is caused by a distinct tobamovirus, for which the name Trichosanthes mottle mosaic virus (TrMMV) is proposed. As the infectious cDNA clone of TrMMV could also infect five other cucurbit crops, this distinct tobamovirus could be a potential threat to other cucurbitaceous crops.